Food packaging materials testing & quality assurance - Singh, Preeti (Boca Raton CRC Press, 2017)
This book is arguably the first one focusing on packaging material testing and quality assurance. Food Packaging Materials: Testing & Quality Assurance provides information to help food scientists, polymer chemists, and packaging technologists find practical solutions to packaging defects and to develop innovative packaging materials for food products. Knowledge of packaging material testing procedures is extremely useful in the development of new packaging materials. Unique among books on packaging, this reference focuses on basic and practical approaches for testing packaging materials. A variety of packaging materials and technologies are being used, with glass, paper, metal, and plastics as the most important groups of materials. Material properties such as mechanical and other physical properties, permeability, sealing, and migration of substances upon food contact are determining factors for food quality, shelf life, and food safety. Therefore, food packaging materials have to be tested to ensure that they have correct properties in terms of permeability for gases, water vapor, and contaminants; of mechanical and other physical properties; and of the thickness of main components and coating layers.


This book has been designed to shed light on food packaging material testing in view of packaging integrity, shelf life of products, and conformity with current regulations. This comprehensive book, written by a team of specialists in the specific areas of food packaging, package testing, and food contact regulations, deals with the problems in a series of well-defined chapters. It covers the relations between packaging properties and shelf life of products and describes testing methods for plastics, metal, glass, and paper, including the areas of vibration, permeation, and migration tests. It will be of benefit for students, scientists, and professionals in the area of food packaging.--Provided by publisher.
Includes bibliographical references and index.
Keywords: Food containers; Food -- Packaging -- Quality control; Packaging -- Testing